Body shape divergence of paradise thread fish (Polynemus paradiseus) collected from different coastal habitats of southern Bangladesh: A multivariate approach for population discrimination - Md Asaduzzaman; Mohammad Zafar Iqbal; Farjana Akter Chamily; Sumi Akter; Md Sadequr Rahman Khan; Li Lian Wong; Sheikh Mustafizur Rahman; Md Moshiur Rahman (Aquaculture and Fisheries, 2025)
The paradise thread fish (Polynemus paradiseus) is a commercially and ecologically important euryhaline fish that primarily lives in diversified coastal and estuarine habitats. A comprehensive understanding of the divergence in body shape and discrimination in population parameters related to habitats is crucial for fisheries management and conservation endeavours. To test whether significant morphological differences exist between P. paradiseus populations inhabiting different coastal environments, a total of 366 individuals (198 male and 168 female) were collected from five distant places over three zones- Cox's Bazar (Bakkhali River) and Chattogram (Karnaphuli River) in the southeast coastal regions, Noakhali (lower Meghna River) in the southcentral zone, and Khulna (Shibsa River) and Borguna (Bishkhali River) in the southwest zones adjacent to the Bay of Bengal, Bangladesh in November 2022. The truss networking and geometric morphometric analysis (GMA) indicated variations in body shape among P. paradiseus individuals induced by sexual dimorphism. Wireframe graphs demonstrated that female individuals had wider dorsal-abdominal parts than males. Using the truss networking dataset for five coastal habitats, multivariate analyses revealed two overlapping clusters: southwest (Borguna and Khulna) populations in one cluster, while central (Noakhali) and southeast (Chattogram and Cox's Bazar) populations form separate clusters. The GMA also illustrated that the Khulna-Borguna population was located near the opposite end of the Chattogram-Cox's Bazar population axis, and the Noakhali populations were somewhat in the middle, with a high degree of overlap. Wireframe graphs displayed a significant body shape variations among populations, mainly in the snout shape, the width of the dorsal-abdominal part, the tail shape, and the head shape. The Discriminant Function Analysis revealed that there were pronounced variations in body shape between two populations located in distant regions, while there were minimum variations between two populations located close to each other. This study underscores the effectiveness of landmark-based truss networking and geometric morphometrics in discerning morphological variations across different habitats. These variations likely hold adaptive significance and are critical for informed population management and conservation strategies in the population structure of euryhaline P. paradisus.